Mycobacterium tuberculosis Rv0991c Is a Redox-Regulated Molecular Chaperone - Samuel H. Becker (American Society for Microbiology, 2020)
ABSTRACT The bacterial pathogen Mycobacterium tuberculosis is the leading cause of death by an infectious disease among humans. Here, we describe a previously uncharacterized M. tuberculosis protein, Rv0991c, as a molecular chaperone that is activated by oxidation. Rv0991c has homologs in most bacterial lineages and appears to function analogously to the well-characterized Escherichia coli redox-regulated chaperone Hsp33, despite a dissimilar protein sequence. Rv0991c is transcriptionally coregulated with hsp60 and hsp70 chaperone genes in M. tuberculosis, suggesting that Rv0991c functions with these chaperones in maintaining protein quality control. Supporting this hypothesis, we found that, like oxidized Hsp33, oxidized Rv0991c prevents the aggregation of a model unfolded protein in vitro and promotes its refolding by the M. tuberculosis Hsp70 chaperone system. Furthermore, Rv0991c interacts with DnaK and can associate with many other M. tuberculosis proteins. We therefore propose that Rv0991c, which we named “Ruc” (redox-regulated protein with unstructured C terminus), represents a founding member of a new chaperone family that protects M. tuberculosis and other species from proteotoxicity during oxidative stress. IMPORTANCE M. tuberculosis infections are responsible for more than 1 million deaths per year. Developing effective strategies to combat this disease requires a greater understanding of M. tuberculosis biology. As in all cells, protein quality control is essential for the viability of M. tuberculosis, which likely faces proteotoxic stress within a host. Here, we identify an M. tuberculosis protein, Ruc, that gains chaperone activity upon oxidation. Ruc represents a previously unrecognized family of redox-regulated chaperones found throughout the bacterial superkingdom. Additionally, we found that oxidized Ruc promotes the protein-folding activity of the essential M. tuberculosis Hsp70 chaperone system. This work contributes to a growing body of evidence that oxidative stress provides a particular strain on cellular protein stability.